SEED MORPHOBIOMETRY AND GERMINATION OF Sesbania punicea (Cav.) Benth. AND Sesbania virgata (Cav.) Pers. - Duarte, Manoela Mendes; Milani, Jaçanan Eloísa de Freitas; Oliveira, Thiago Wendling Goncalves de; Blum, Christopher Thomas; Nogueira, Antonio Carlos (Floresta, 2019)
Belonging to the family Fabaceae, Sesbania punicia and S. virgata are characterized by their ecological potential in the recovery of degraded areas. The present study aimed to describe the physical, morphobiometric characteristics of seeds, the germination phases and the initial development of S. punicia and S. virgata seedlings, as well as the germination behavior of seeds at different temperatures and substrates. For the physical characterization of seeds, the weight of one thousand seeds, number of seeds per kilogram, dry biomass of one thousand seeds and the moisture content were determined. To evaluate the effect of substrate and temperature on germination, the experiment was conducted in a completely randomized design, using a 3 x 3 factorial scheme, three substrates (sand, vermiculite and blotting paper) and three temperatures (20, 25 and 30 °C). The following factors were evaluated: germination percentage, germination speed index, mean germination time and synchronization index. S. punicea presented 13,243 seeds and S. virgata presented 14,414 seeds per kilogram, with moisture content of 14.5 and 7.9 %, respectively. Both species present similar morphobiometry and seedling development. For S. punicea, the blotting paper substrate and the temperature of 25 °C were most efficient for germination. For S. virgata, all treatments were effective for germination.